Bioregion heterogeneity correlates with extensive mitochondrial DNA diversity in the Namaqua rock mouse, Micaelamys namaquensis (Rodentia: Muridae) from southern Africa - evidence for a species complex - Russo Isa-Rita M; Chimimba Christian T; Bloomer Paulette (BMC Evolutionary Biology, 2010)
Abstract Background Intraspecific variation within the diverse southern African murine rodents has not been extensively investigated, yet cryptic diversity is evident in several taxa studied to date. The Namaqua rock mouse, Micaelamys namaquensis Smith, 1834 is a widespread endemic murine rodent from the subregion. Currently, a single species with four subspecies is recognised, but in the past up to 16 subspecies were described. Thus, this species is a good candidate for the investigation of patterns and processes of diversification in a diverse but under-studied mammalian subfamily and geographic region. Here, we report genetic differentiation based on mitochondrial DNA (mtDNA) cytochrome b (cyt b) sequences among samples collected over an extensive coverage of the species' range. Results Cytochrome b sequences of 360 widely sampled individuals identified 137 unique maternal alleles. Gene tree and phylogeographic analyses of these alleles suggest the presence of at least eight lineages or haplogroups (A-H), with varying degrees of intra-lineage diversity. This differentiation is in contrast with the most recent taxonomic treatment based on cranial morphometrics which only recognised four subspecies. The mtDNA diversity strongly supports earlier views that this taxon may represent a species complex. We further show statistical support for the association of several of these lineages with particular vegetation biomes of southern Africa. The time to the most recent common ancestor (TMRCA) dates to the Pliocene (~5 Mya) whereas coalescent-based divergence time estimates between lineages vary between 813 Kya [0.22 - 1.36] and 4.06 Mya [1.21 - 4.47]. The major diversification within lineages occurred during the Pleistocene. The identification of several regions of sympatry of distinct lineages offers future opportunities for the elucidation of the underlying speciation processes in the suggested species complex. Conclusions Similar to other African murine rodents, M. namaquensis radiated during the Pliocene and Pleistocene coinciding with major periods of aridification and the expansion of savanna habitats. The suggested species complex is represented by at least eight lineages of which the majority are confined to only one or a few neighbouring biomes/bioregions. Contrasting intra-lineage phylogeographic patterns suggest differences in adaptation and responses to Plio-Pleistocene climatic and vegetation changes. The role of ecological factors in driving speciation in the group needs further investigation.